Managing Inclusiveness and Diversity in Teams: How Leader Inclusiveness Affects Performance through Status and Team Identity - Mitchell, Rebecca; Boyle, Brendan; Parker, Vicki; Giles, Michelle; Chiang, Vico; Joyce, Pauline (Human Resource Management, 2015)
While there is increasing pressure to work collaboratively in interprofessional teams, health professionals often continue to operate in uni‐professional silos. Leader inclusiveness is directed toward encouraging and valuing the different viewpoints of diverse members within team interactions, and has significant potential to overcome barriers to interprofessional team performance. In order to better understand the influence of leader inclusiveness, we develop and investigate a model of its effect incorporating two mediated pathways. We predict that leader inclusiveness enhances interprofessional team performance through an increase in shared team identity and a reduction in perceived status differences, and we argue that the latter pathway is contingent on professional diversity. Data from 346 members of 75 teams support our model, with team identity and perceived status differences mediating a significant effect of leader inclusiveness on performance. In addition, we found support for the moderating role of professional diversity. The results reinforce the critical role of leader inclusiveness in diverse teams, particularly interprofessional teams, and suggest that social identity and perceived status differences are critical factors mediating its impact on performance. © 2015 Wiley Periodicals, Inc.